Direct and Mediated Effects of Cognitive Function with Multidimensional Outcome Measures in Schizophrenia: The Role of Functional Capacity - Ho, Jennifer S. (2013)
Although cognitive ability is a known predictor of real-world functioning in schizophrenia, there has been an expanded interest in understanding the mechanisms by which it explains real-world functioning in this population. We examined the extent to which functional capacity (i.e., skills necessary to live independently) mediated the relationship between cognitive ability and both observer and self-reported real-world functioning in 138 outpatients with schizophrenia. Functional capacity significantly mediated the relations between cognitive ability and observer rated real world functioning, but not self-reported real world functioning, with small to medium effect sizes observed for all outcomes. The role of cognitive ability in observer vs. self-reported real-world functioning may be explained by different mechanisms.